Highly sensitive and selective detection of Al(III) ions in aqueous buffered solution with fluorescent peptide-based sensor. Issue 18 (15th September 2016) - In, Byunggyu; Hwang, Gi Won; Lee, Keun-Hyeung
Graphical abstract: A fluorescent sensor based on a tripeptide (SerGluGlu) detected selectively and sensitively Al(III) among 16 metal ions in aqueous buffered solutions. Abstract: A fluorescent sensor based on a tripeptide (SerGluGlu) with a dansyl fluorophore detected selectively Al(III) among 16 metal ions in aqueous buffered solutions without any organic cosolvent. The peptide-based sensor showed a highly sensitive turn on response to aluminium ion with high binding affinity (1.84 × 10 4  M −1 ) in aqueous buffered solutions. The detection limit (230 nM, 5.98 ppb) of the peptide-based sensor was much lower than the maximum allowable level (7.41 μM) of aluminium ions in drinking water demanded by EPA. The binding mode of the peptide sensor with aluminium ions was characterized using ESI mass spectrometry, NMR titration, and pH titration experiments.